Information systems and services for small and medium scale industries in developing countries - Neelameghan, A (Unesco Port of SpainTT, 1994)
Provides an overview of the business environment in which small and medium scale industries operate. Introduces the information intermediary to the functions and operations of a small or medium scale industry. Provides guidelines for developing the required skills in information analysis aand consolidation.